Collaborative governance in enhancing community welfare through regional flagship programs: a study of tanah datar regency - Malse Yulivestra; M. Ichsan Kabullah; Ratih Ratih; Chairunnisa -; Novalinda - (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This study analyzes the implementation of the Ansell and Gash collaborative governance model in the Tanah Datar Regency flagship programs (Progul) and its contribution to community welfare and poverty alleviation. A qualitative case study was conducted using in-depth interviews with 22 informants, supported by observations and document analysis. Data were analyzed using the Miles and Huberman interactive model based on six collaborative governance dimensions. The findings show that all six dimensions were effectively implemented. The programs increased agricultural productivity, expanded access to 1.5% low-interest business credit, produced around 5,000 Qur'an memorizers, and significantly reduced telecommunications blank spots. However, these achievements have not yet significantly reduced the regional poverty rate. Collaborative governance strengthens program implementation, while customary institutions emerge as a crucial collaborative element for sustainable poverty alleviation in the Minangkabau nagari context.